2016
DOI: 10.1016/j.canlet.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of the interaction between cancer cell-derived chemokine, CCL4, and intra-bone CCR5-expressing fibroblasts in breast cancer bone metastasis

Abstract: From a murine breast cancer cell line, 4T1, we established a subclone, 4T1.3, which consistently metastasizes to bone upon its injection into the mammary fat pad. 4T1.3 clone exhibited similar proliferation rate and migration capacity as the parental clone. However, the intra-bone injection of 4T1.3 clone caused larger tumors than that of the parental cells, accompanied with increases in fibroblast, but not osteoclast or osteoblast numbers. 4T1.3clone displayed an enhanced expression of a chemokine, CCL4, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 44 publications
4
67
0
Order By: Relevance
“…However, a previous study reported that higher levels of CCL2 in ovarian cancer cell lines were associated with increased chemosensitivity and decreased invasion in vitro, and increased ovarian tumoral expression of CCL2 was associated with improved chemotherapy response and survival outcomes . In addition, the CCL4 axis can contribute to breast cancer metastasis to bone by mediating the interaction between cancer cells and fibroblasts in bone cavity by bonding to CC chemokine receptor type 5 . Inversely, increased CCL4 expression shows a significant association with prolonged OS in patients with esophageal squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study reported that higher levels of CCL2 in ovarian cancer cell lines were associated with increased chemosensitivity and decreased invasion in vitro, and increased ovarian tumoral expression of CCL2 was associated with improved chemotherapy response and survival outcomes . In addition, the CCL4 axis can contribute to breast cancer metastasis to bone by mediating the interaction between cancer cells and fibroblasts in bone cavity by bonding to CC chemokine receptor type 5 . Inversely, increased CCL4 expression shows a significant association with prolonged OS in patients with esophageal squamous cell carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and treatment history were evaluated in relationship with cancer outcomes and pro-inflammatory cytokine profiles. A biomarker correlation analysis was performed between the studied C-C chemokines and between each of them and the cytokine levels already reported elsewhere for this particular patient population [1], [2], [3], [4], [5], [6], [7], [8], [9]. The additional correlations were provided for completeness and usability of this data.Data source locationUnited States, Buffalo, NY - 42Ā° 53׳ 50.3592"N; 78Ā° 52׳ 2.658"WData accessibilityThe data is with this article…”
mentioning
confidence: 99%
“…Their mobilization is a chemotactic response mediated by tumor-derived factors, among which the Cā€“C chemokines CCL-2, 3, 4, and 5 [4], [5], [6], [7], [8], [9]The combined contribution of CCL-2, 3, 4, and 5 is responsible for the vast functionality of the macrophage phenotypes in response to changing environmental stimuli [4], [5], [6], [7], [8]This dataset represents the observed relationship between injectable insulin use, circulating pro-inflammatory Cā€“C chemokines at breast cancer diagnosis and outcomesReported data has the potential to guide future studies evaluating the impact of insulin-regulated signaling on activation of tumor-associated macrophages in breast cancerOur observations can assist further research clarifying the role of insulin in the regulation of the pro-inflammatory signaling leading to pro-tumorigenic activity in the breast tumor microenvironment…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47 CCR5 also contributes to breast cancer metastasis to bone by mediating the interaction between cancer cells and fibroblasts in the bone cavity. 48 As with most chemokines, CCR5 undergoes palmitoylation at three cysteine residues within its C-terminal region. In immune cells, palmitoylation controls transport of the receptor to the cell surface and its interaction with signaling pathways.…”
Section: Introductionmentioning
confidence: 99%